Increase in driving after cocaine use in Spain: a cross-sectional dataset analysis for 2021 - García-Mingo, Mercedes; Martín-Fernández, Marta; Gutiérrez-Abejón, Eduardo; Álvarez, F. Javier (Frontiers in Public Health, 2023)
Objective Driving under the influence of alcohol and/or drugs impairs skills essential for safe driving, increases the risk of being involved in a traffic accident and is particularly prevalent in Spain. The aim is to assess the prevalence of positive substance driving cases, what factors may be associated with driving after substance use, and the evolution of the progress in the prevalence of drug use among drivers in drivers based on the 2008, 2013, 2018, and 2021 studies. Study design and setting The present study was conducted in a representative sample of Spanish drivers in 2021 for alcohol (breath) and psychoactive substances [oral fluid (OF)]. The sample size was 2980 drivers, mostly males (76.5%) with a mean age of 41.35 ± 13.34 years. Results In 2021, 9.3% of drivers tested positive for alcohol and/or drugs. The presence of alcohol alone was observed in 4.2% of drivers, alcohol and another substance in 0.3%, a single drug in 4.4%, and two or drugs other than alcohol in 0.4%. Overall, cocaine cases were the highest registered in 2021 (2.4%), while cannabis (1.9%) and polydrug cases (0.7%) were the lowest, with respect to the 2008/2013/2018 studies. Conclusions According to our research, in 2021, 9 out of 100 drivers were detected to have some substance in their system. This prevalence remains unacceptably high in Spain, with a marked increase in the frequency of driving after cocaine use. Further interventions and measures must be taken to avoid driving under the influence of alcohol and/or drugs.